Tax harmonization in the European Union and the eurozone: a multilateral analysis of tax systems - Sonja Engeli Pippin; Mehmet Serkan Tosun (Financial Theory and Practice, 2016)

(untitled)
This exploratory study takes a new look at the tax systems of countries in the Organisation of Economic Co-operation and Development (OECD). We measure a country’s tax system using time-series cross-sectional data on tax collection variables as well as a cross-sectional metric assessing tax administration and enforcement. More specifically, we examine the countries’ (i) overall tax burden, (ii) income tax reliance, and (iii) fiscal decentralization as well as some “non-rate” variables related to tax administration and enforcement. The purpose is to compare European Union (EU) member states and those countries in the eurozone with other OECD countries and over time in order to test (1) whether EU member states and eurozone countries have tax systems that are more similar to each other than to other countries, and (2) whether some tax harmonization is taking place - within the EU (eurozone) and other countries. The descriptive analysis and graphical representation, as well as first empirical tests, show that the tax systems of EU member states and eurozone countries are significantly different from other countries’tax systems. Yet, we do not find much tax harmonization in the EU (eurozone) countries over time. Future research might delve more into the question what drives harmonization with the intention of eventually formulating policy strategies.